Application of Steganography for Inserting Text Messages in Digital Images Using the Least Significant Bit Method - Nasrullah Akbar Ramadhani; Indah Susilawati (LPPM Universitas Mercu Buana Yogyakarta, 2020)
The development of digital media (Internet, electronic mail, and so on) gas data is already common, along with such developments, crimes in the field of information technology and telecommunication increasingly occur. Digital data commonly used is digital imagery, digital imagery that is transmitted through the media can be important data, so there is a problem arises how to secure digital imagery is confidential. One ofhis ways is steganography. The goal in this study inserts text messages using a steganography technique with the Least Significant Bit method on the digital Image media. The Least Significant Bit Method performs the insertion of a text message into a digital image by changing the value of the pixel to 8 bits then taking the leading 4 bits to be inserted at 4 the last bit at 8 bit pixels, the process of inserting a text message on digital imagery will be divided into three layers namely layer Red, layer Green, layer Blue . Once the digital image is saved, the extract process is aimed at retrieving text messages that are already stored in the digital image. In this test there are two images used that image size 325x325 pixels and image size 473x354 pixels each image is performed three times the insertion of text messages different number of characters ranging from three words to one paragraph. The image encryption process that becomes the container is not significantly different from the original, for image description results that have been inserted in a hidden text message can be returned with a change in the pixel value that does not alter the image Significant.